2013
DOI: 10.1086/bblv224n3p156
|View full text |Cite
|
Sign up to set email alerts
|

Species-Specificity of Sperm Motility Activation and Chemotaxis: a Study on Ascidian Species

Abstract: Egg-derived sperm-activating factors and attractants activate sperm motility and attract the sperm, respectively. These phenomena constitute the first communication signaling between males and females in the process of fertilization in many animals and plants, and in many cases, these are species-specific events. Thus, sperm motility activation and chemotaxis may act as a safety process for the authentication between conspecific egg and sperm, and help to prevent crossbreeding. Here, we examine species-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…Sperm chemotaxis appears to be a much more specifi c phenomenon at the species or genus level in many animal species: cnidarians (Miller 1979 ), echinoderms other than sea urchins (Miller 1985a(Miller , 1997, and ascidians (Miller 1982 ;Yoshida et al 2013 ). These results indicate that the specifi city of sperm chemotaxis participates in the prevention of crossbreeding at fertilization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sperm chemotaxis appears to be a much more specifi c phenomenon at the species or genus level in many animal species: cnidarians (Miller 1979 ), echinoderms other than sea urchins (Miller 1985a(Miller , 1997, and ascidians (Miller 1982 ;Yoshida et al 2013 ). These results indicate that the specifi city of sperm chemotaxis participates in the prevention of crossbreeding at fertilization.…”
Section: Resultsmentioning
confidence: 99%
“…Research into the precise chemical nature of sperm attractants and their corresponding receptors in different species may provide new horizons for studies of the fertilization system, especially on the mechanisms by which authentic interactions between conspecifi c eggs and spermatozoa occur. Yoshida et al ( 2013 ) …”
Section: Resultsmentioning
confidence: 99%
“…Daphnia males ejaculate into the brood pouch filled with water (the same used for our observation); it is therefore likely that the absence of motility observed in water on a microscope slide reflects what is happening in the brood pouch. However, it has been shown that fluid surrounding eggs of externally fertilized species induced modification to sperm motility (Yoshida et al , 2013). In such scenario, the capsule might break, the sperm would attach to the oocyte, crawl to an eventual specific fusion site and larger sperm with filaments may be advantageous in the race to this site.…”
Section: Discussionmentioning
confidence: 99%
“…Our knowledge about sperm is vast, yet mostly compartmentalized, and does not cross interdisciplinary borders. For example, even though sperm chemotaxis has been described across most kingdoms (Yoshida et al 2013), a comprehensive quantitative picture of sperm navigation and the underlying signalling mechanism has been advanced for only few model systems, such as marine invertebrates (Guerrero et al 2010; Hirohashi et al 2013; Kaupp and Alvarez 2016; Yoshida and Yoshida 2011; Zimmer and Riffell 2011), mammalian sperm (Bukatin et al 2015; Eisenbach and Giojalas 2006; Kaupp and Strünker 2017; Miki and Clapham 2013), some fish (Fechner et al 2015; Yanagimachi et al 2013), and bracken fern (Brokaw 1958, 1973). For insects, most studies have addressed only morphological and evolutionary aspects.…”
Section: Discussionmentioning
confidence: 99%